ПРОТИВОДЕЙСТВИЕ ИСПОЛЬЗОВАНИЮ ДЕТЕЙ В ЦЕЛЯХ СОВЕРШЕНИЯ УБИЙСТВ ЭКСТРЕМИСТСКИМИ И ТЕРРОРИСТИЧЕСКИМИ ГРУППАМИ - Румянцева, Антонина Владимировна (SUPREMANCE OF LAW, 2017)
The article discusses the problem of child involvement in serious crimes. Analyzed ways to counter the use of minors to commit murders of extremist and terrorist groups. Draw conclusions on the necessity of adopting a comprehensive, science-based measures to combat this type of crime.
Keywords: counteraction; international terrorism; children; minors; terrorist organizations; protection of rights